2019
DOI: 10.1002/jsp2.1060
|View full text |Cite
|
Sign up to set email alerts
|

A novel magnetic resonance imaging postprocessing technique for the assessment of intervertebral disc degeneration—Correlation with histological grading in a rabbit disc degeneration model

Abstract: Introduction Estimation of intervertebral disc degeneration on magnetic resonance imaging (MRI) is challenging. Qualitative schemes used in clinical practice correlate poorly with pain and quantitative techniques have not entered widespread clinical use. Methods As part of a prior study, 25 New Zealand white rabbits underwent annular puncture to induce disc degeneration in 50 noncontiguous lumbar discs. At 16 weeks, the animals underwent multi‐echo T2 MRI scanning and were euthanized. The discs were stained an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Because rabbits are commonly used species in induced IVDD models, quantitative analysis of degeneration is a useful tool in examination and interpretation of results. Sheldrick et al found decay variance mapping of multi-echo transverse relaxation time (T2) MRI scanning on rabbits to be a beneficial quantitative analysis method with higher sensitivity and specificity than T2 relaxometry for disc puncture models [ 155 ].…”
Section: Insights From Different Speciesmentioning
confidence: 99%
“…Because rabbits are commonly used species in induced IVDD models, quantitative analysis of degeneration is a useful tool in examination and interpretation of results. Sheldrick et al found decay variance mapping of multi-echo transverse relaxation time (T2) MRI scanning on rabbits to be a beneficial quantitative analysis method with higher sensitivity and specificity than T2 relaxometry for disc puncture models [ 155 ].…”
Section: Insights From Different Speciesmentioning
confidence: 99%